Abacus as Educational Media: Collaboration between Parents and Children in the Development of Numeracy Skills - Febriani, Ratu Eva; Yusnida, Yusnida (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service activity aims to improve the numeracy skills of children living in RT 6 Kebun Keling Village, Teluk Segara District, Bengkulu City, by using abacus training as an educational tool. The methodology applied is counseling in the form of lectures that are strengthened by discussions and questions and answers, complemented by practice and simulations of learning assistance by parents. The findings showed that incorporating abacus into the learning framework significantly improved children's numeracy skills, with 75% of participants successfully completing counting tasks using abacus. In addition, proactive parental involvement has been shown to increase their confidence in facilitating their child's learning process at home, as evidenced by 65% of parents who expressed their ability to support their child's learning efforts. This initiative not only strengthens children's numeracy skills but also fosters a constructive emotional bond between parents and children. In summary, synergies between parents, children, and educators facilitated through play-based methodologies such as abacus have shown effectiveness in improving numeracy skills while fostering a fun learning atmosphere. The sustainable development of this activity is recommended to improve the quality of early childhood education.